PEMAHAMAN MAHASISWA PGSD TERHADAP IMPLEMENTASI NILAI-NILAI PANCASILA - Muchtar; Putri Mahanani; M. Imron Rosyadi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2015)
Abstract: This survey study was intended to describe the students’ understanding of the values of the Pancasila in the life of the nation. The samples of the study were all active students of 2015/2016 academic year. The data was collected by using questionnaire and was analyzed by using percentage technique. The results of the study showed that the students’ understanding of the values of the Pancasila in their national life was fulfilled the criteria of good enough. The students had not fully understood the implementation of the values of Pancasila in the daily life. Abstrak: Penelitian survey ini bertujuan untuk mendeskripsikan pemahaman mahasiswa tentang penerapan nilai-nilai Pancasila dalam kehidupan berbangsa. Sampel penelitian adalah mahasiswa angkatan 2015/2016 dari seluruh mahasiswa aktif. Data dikumpulkan melalui angket dan dianalisis dengan teknik persentase. Hasil penelitian menunjukkan pemahaman mahasiswa tentang penerapan nilai-nilai Pancasila dalam kehidupan berbangsa termasuk kriteria cukup baik. Mahasiswa belum sepenuhnya memahami pelaksanaan nilai-nilai Pancasila dalam kehidupan sehari-hari.